ECOLOGICAL WOOD ANATOMY OF Blepharocalyx salicifolius (H. B. K.) Berg - Denardi, Luciano (2005)
The purpose of this work is the comparison of the wood anatomy of Blepharocalyx salicifolius (H. B. K.) Berg (Myrtaceae) from two provenances in the State of Rio Grande do Sul. There were collected 6 samples of wood; three from “Serra do Sudeste” and the others from “Campos de Cima da Serra”. The wood anatomical features did not express relevant differences between provenances, with the exception of pith flecks. With respect to the quantitative features, on the other hand, there were found important differences in the structure of vessels, axial parenchyma, rays and fibres. For the “Serra do Sudeste” samples, there were found xeric evidences in the wood: a larger number of small vessels, besides shorter vessel members and fibres, in comparison with those from the “Campos de Cima da Serra” region. The differences in the wood anatomy may be interpreted as adaptative responses to environmental conditions.